On-Surface Synthesis of Non-Benzenoid Nanographenes Embedding Azulene and Stone-Wales Topologies - Biswas, Kalyan; Chen, Qifan; Obermann, Sebastian; Ma, Ji; Soler-Polo, Diego; Melidonie, Jason; Barragán, Ana; Sánchez-Grande, Ana; Lauwaet, Koen; Gallego, José M; Miranda, Rodolfo; Écija, David; et al. (Angewandte Chemie (International ed. in English), 2024)
The incorporation of non-benzenoid motifs in graphene nanostructures significantly impacts their properties, making them attractive for applications in carbon-based electronics. However, understanding how specific non-benzenoid structures influence their properties remains limited, and further investigations are needed to fully comprehend their implications. Here, we report an on-surface synthetic strategy toward fabricating non-benzenoid nanographenes containing different combinations of pentagonal and heptagonal rings. Their structure and electronic properties were investigated via scanning tunneling microscopy and spectroscopy, complemented by computational investigations. After thermal activation of the precursor P on the Au(111) surface, we detected two major nanographene products. Nanographene Aa-a embeds two azulene units formed through oxidative ring-closure of methyl substituents, while Aa-s contains one azulene unit and one Stone-Wales defect, formed by the combination of oxidative ring-closure and skeletal ring-rearrangement reactions. Aa-a exhibits an antiferromagnetic ground state with the highest magnetic exchange coupling reported up to date for a non-benzenoid containing nanographene, coexisting with side-products with closed shell configurations resulted from the combination of ring-closure and ring-rearragement reactions (Ba-a , Ba-s , Bs-a and Bs-s ). Our results provide insights into the single gold atom assisted synthesis of novel NGs containing non-benzenoid motifs and their tailored electronic/magnetic properties.
Keywords: Scanning tunnelling microscopy; Nanographenes; Open-shell species; Oxidative ring-closure; Azulene and Stone-Wales defects